NILAI ISLAM DALAM RITUS KEHIDUPAN ORANG MELAYU DI KOTA BENGKULU - Samsudin Samsudin (JURNAL ILMIAH SYI'AR, 2016)
Culture melayu Bengkulu is majority with the spirit of Islamic values? Are articulatedand manifested in local culture certain rites, such as religious ceremonies, life cycle(cycle rites), and every activity of the Malayu city of Bengkulu. Akultuirasi andinherensi both become a way of life for the survival of cultural and religious socialBengkulu Malay society.